Development of LKPD Through the RADEC Model to Improve Learning Outcomes of Pancasila Education for Class IV SDN 064990 Medan Johor - Simanullang, Reno Francius; Dharma, Surya; Sri Milfayetty, Sri (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study develops Student Worksheets (LKPD) based on the RADEC (Read, Answer, Discuss, Explain, Create) learning model to improve learning outcomes of Pancasila Education on the material "Cooperation in My Environment" for fourth grade students of SDN 064990 Medan Johor. This study uses an R&D approach with the 4D model (Define, Design, Develop), without the Disseminate stage due to time constraints. Data collection includes expert validation of questionnaires, teacher and student response surveys, and pretests and posttests. Data analysis uses quantitative descriptive methods (SPSS and N-Gain). The validation results show that LKPD is very feasible in terms of content (86.11%), design (92.85%), and language (81.94%). The practical test produced very positive responses from teachers (92.7%) and students (88.3%). LKPD is proven to be effective in improving learning outcomes with an N-Gain score of 42.86% (moderate category). RADEC-based LKPD also succeeded in increasing character values ​​and 21st century skills (collaboration, critical thinking, creativity). In conclusion, RADEC-based LKPD is very valid, practical, and quite effective for Pancasila Education learning, and can be replicated and become a reference for innovation in the Merdeka Curriculum